2017
DOI: 10.1002/admi.201700599
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Distribution of Magnetic Anisotropies in Bimagnetic Soft Core–Hard Shell MnFe2O4@CoFe2O4 Nanoparticles

Abstract: The nanoscale distribution of magnetic anisotropies was measured in core@shell MnFe2O4@CoFe2O4 7.0 nm particles using a combination of element selective magnetic spectroscopies with different probing depths. As this picture is not accessible by any other 2 technique, emergent magnetic properties were revealed. The coercive field is not constant in a whole nanospinel. The very thin (0.5 nm) CoFe2O4 hard shell imposes a strong magnetic anisotropy to the otherwise very soft MnFe2O4 core: a large gradient in coerc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Sensitivity of RIXS-MCD spectra to different elements and crystal sites provides a straightforward way to disentangle individual contributions to magnetization, which has been recently used for the selective determination of magnetic anisotropy in core/shell and mixed ferrite nanoparticle systems. 45,48,57 Here we verify whether it can be applied to separate magnetization profiles of SPION from that of the carrier liquid. Results of the measurements performed at room temperature on Zn 0.53 Fe 2.47 O 4 nanoparticles suspended in water are shown in Fig.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Sensitivity of RIXS-MCD spectra to different elements and crystal sites provides a straightforward way to disentangle individual contributions to magnetization, which has been recently used for the selective determination of magnetic anisotropy in core/shell and mixed ferrite nanoparticle systems. 45,48,57 Here we verify whether it can be applied to separate magnetization profiles of SPION from that of the carrier liquid. Results of the measurements performed at room temperature on Zn 0.53 Fe 2.47 O 4 nanoparticles suspended in water are shown in Fig.…”
mentioning
confidence: 87%
“…46,47 However, it has been recently shown that selective magnetization profiles can be probed on frozen SPION suspensions by means of hard X-ray Magnetic Circular Dichroism combined with Resonant Inelastic X-ray Scattering (RIXS-MCD). 48 Here we report on the feasibility of using 1s2p RIXS-MCD, a photon-in/photon-out spectroscopy that probes intensity of 2p emission upon resonant excitation of 1s electrons, for the selective characterization of structural and magnetic properties of SPION in suspensions.…”
mentioning
confidence: 99%
“…The probing depth is about a few μm versus a few nm for soft X-rays when using total electron yield, which ensures that the whole volume, and not only the outermost part, is probed. The bulk sensitivity has been recently exploited in the RIXS-MCD characterization of various nanosized materials where it was needed to access the entire volume: from buried thin films of a few tens of nm 92 to bimagnetic core-shell NPs in powder 93 and liquid phase 94 or even binary ferrofluids composed of two magnetically different types of NPs. 95 The magneto-spectroscopy RIXS-MCD is indeed very well suited for investigating magnetic colloidal NPs in the liquid phase.…”
Section: Colloidal Nanoparticlesmentioning
confidence: 99%
“…The second example of application of RIXS-MCD on magnetic NPs in the liquid phase is given by the study of 7 nm core-shell MnFe 2 O 4 @CoFe 2 O 4 NPs performed by N. Daffé and co-workers. 94 The magnetic properties of spinel ferrite colloidal NPs can be tuned further by combining deliberately two different phases in a core-shell structure. The idea is to modulate the magnetic anisotropy to enhance the performance in selected applications.…”
Section: Colloidal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation